What is Open Access Button? An interview with Joe McArthur. Issue 3 (17th November 2017) - Cook, Eleanor I.; McArthur, Joe
ABSTRACT: Articles published behind a paywall in commercial journals are often inaccessible to potential readers who are not affiliated with a subscribing institution. Open Access Button is an application that assists readers in finding Open Access versions of such articles. This service works in a completely legal fashion. This interview is with one of the co-founders of the service, Joe McArthur. Open Access Button is supported by the Scholarly Publishing and Academic Resources Coalition.